Innovative applications of micro and nanoencapsulation in food packaging - Ozdemir, Murat; Kemerli, Tansel (John Wiley & Sons Ltd, 2016)
[No abstract available]
Keywords: Escherichia-Coli O157-H7; Liposome-Encapsulated Nisin; Controlled-Release; Essential Oils; Beta-Cyclodextrin; In-Situ; Microencapsulating Properties; Antibacterial Activity; Antimicrobial Activity; Bovine Lactoferrin